Pengaruh Ekstrak Etanol Daun Kenikir (Cosmos caudatus Kunth.) terhadap Kerusakan Struktur Histologis Ginjal Mencit (Mus musculus L.) yang Diinduksi Parasetamol - Lina Kristanti Wibowo; . Suyatmi; Yulia Sari (Nexus Biomedika, 2014)
Background: Kenikir leaves contain various kind of antioxidants, such as vitamin C, ?-carotene, minerals, and polyphenols which are known to protect kidneys from oxidative stress caused by free radical exposure. The purpose of this study is to evaluate the nephroprotective effect of Kenikir leaf extract toward histological damage of the mice's kidney cells induced by Parasetamol. Methods: This was a laboratory experimental study with the posttest only controlled group design. The samples were 35-Swiss webster male mice, aged 2-3 months, and weight about 20 gram. Samples were divided into five groups randomly. Normal group (KN) was given distilled water and Negative control (KK(-)) was given Parasetamol. Extract dosage of 2.8 mg, 5.6 mg, and 11.2 mg of kenikir leaves were given daily for 14 days to treatment group 1 (KP1), treatmen group 2 (KP2), and treatment group 3 (KP3), respectively. A toxic dosage of Parasetamol as much as 5.07 mg, was given to negative control group and treatment groups on day 12th, 13th, and 14th. On day 15th , mice were sacrificed by neck dislocation. The kidneys were taken for histological preparation and stained with HE. The histological damage was assessed based on quantifying the pyknosis, karyorrhexis, and karyolysis on 50 proximal tubuli of epithelial cells. The data were analyzed using One-way ANOVA test (? = 0.05) and Post Hoc Multiple Comparisons test (? = 0.05). Results: The most damaged cells were found in KK(-) and the least in KN. The significant difference was observed among groups (One-way ANOVA test p = 0.000). The significant difference was observed between groups (Post Hoc test p = 0.000). They were KN-KK(-), KN-KP1, KN-KP2, KN-KP3, KK(-)-KP1, KK(-)-KP2, KK(-)-KP3, KP1-KP2, KP1-KP3, and KP2-KP3. Conclusions: Ethanol extract of Kenikir leaves can prevent the histological damage of the mice's kidney cell induced by Parasetamol. The increasing dose of the extract is followed by the increase of protective effect. Keywords: Kenikir leaves, histological damage, mice's kidney, Parasetamol